Chrysophanol Attenuates Manifestations of Immune Bowel Diseases by Regulation of Colorectal Cells and T Cells Activation in Vivo - Hyun-Su Lee (Molecules, 2021)
Inflammatory bowel disease (IBD) is an immune disorder that develops due to chronic inflammation in several cells. It is known that colorectal and T cells are mainly involved in the pathogenesis of IBD. Chrysophanol is an anthraquinone family member that possesses several bioactivities, including anti-diabetic, anti-tumor, and inhibitory effects on T cell activation. However, it is unknown whether chrysophanol suppresses the activity of colorectal cells. In this study, we found that chrysophanol did not induce cytotoxicity in HT-29 colorectal cells. Pre-treatment with chrysophanol inhibited the mRNA levels of pro-inflammatory cytokines in tumor necrosis factor-α (TNF-α)-stimulated HT-29 cells. Western blot analysis revealed that pre-treatment with chrysophanol mitigates p65 translocation and the mitogen-activated protein kinase (MAPK) pathway in activated HT-29 cells. Results from the in vivo experiment confirmed that oral administration of chrysophanol protects mice from dextran sulfate sodium (DSS)-induced IBD. Chrysophanol administration attenuates the expression of pro-inflammatory cytokines in colon tissues of the DSS-induced IBD model. In addition, we found that oral administration of chrysophanol systemically decreased the expression of effector cytokines from mesenteric lymph nodes. Therefore, these data suggest that chrysophanol has a potent modulatory effect on colorectal cells as well as exhibiting a beneficial potential for curing IBD in vivo.